Circular Economy Approaches in the Palm Oil Industry: Enhancing Profitability through Waste Reduction and Product Diversification - Siagian, Utjok Welo Risma; Wenten, I Gede; Khoiruddin, Khoiruddin (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Today, facing difficult environmental and sustainability questions, the palm oil industry is an important force in global trade and development. As a transformative solution to these problems, this review assesses the implementation of circular economy (CE) strategies. CE principles promote the transformation of waste into value through recycling, upcycling and other low-carbon innovation applications. This review estimates the capability of palm-based biomass, including palm oil mill effluent (POME) and refinery wastes. It evaluates how different technologies such as gasification are used to change these fuel sources into energy fuels and value-added products for industry. It also involves incorporating Industry 4.0 to boost efficiency and waste value creation into the operation. Although the potential of CE in creating an eco-friendly, profitable palm oil industry is apparent, nevertheless it must overcome all kinds and levels of barriers – from economic to technological to social. This review points out for collaborative efforts, technological advancement, and supportive policies to navigate these challenges, advocating for a unified shift towards sustainability and efficiency in the palm oil sector.